The United Nations Sustainable Development Goals, Criminology and Criminal Justice: Gorazd Meško, Sanja Kutnjak Ivković, Rok Hacin (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
This chapter provides an overview of the United Nations Sustainable Development Goals (SDGs) and discusses the link between the SDGs and criminal justice systems. We utilise the 2016 Stockholm Resilience Centre classification of SDGs into three categories: 1) biosphere SDGs, 2) economy SDGs, and 3) society SDGs, to discuss the SDGs and provide examples of criminology and criminal justice research that fit each SDG. The main topics covered in this chapter relate to the understanding of deviance and crime (e.g., juvenile delinquency, sexual harassment, hate crimes, rural crime, organised crime, illegal production of drugs, white collar crimes, illegal construction, war and environmental crime) and social reaction to crimes (e.g., tolerance of sexual harassment, acceptance of illegal building), as well as the exploration of law enforcement and discussion of various policing models (e.g., community policing, proactive policing, gender perspectives in policing).